Strategic Student Management for Optimizing Student Council Organizational Performance - Sudirman Sudirman; Saparudin Saparudin; Hilmawati Hilmawati (Journal of Educational Management Research, 2026)
This study aims to examine the role of student management in improving the performance of the Student Council as a school-based organization. A qualitative approach with a case study design was employed to obtain an in-depth understanding of planning, implementation, training, supervision, and evaluation practices in student organizational development. Data were collected through semi-structured interviews, non-participant observation, and documentation, involving school leaders, student affairs personnel, organization supervisors, and student representatives. The findings reveal that student management contributes positively to organizational performance through structured planning, systematic selection, leadership training, mentoring, discipline formation, and continuous evaluation. The implementation of leadership programs and regular coaching encourages students to develop responsibility, cooperation, commitment, and organizational skills. However, several challenges remain, including limited student independence, uneven participation, and the need for stronger coordination between academic and organizational activities. The study implies that effective student management should not only regulate student administration but also function as a strategic instrument for strengthening leadership, character, and participatory organizational culture.